Pengembangan Lembar Kerja Siswa Matematika Berbasis Penemuan Terbimbing Untuk Siswa Kelas VII Sekolah Menengah Pertama Pada Materi Segiempat - Veta Fitriani; Lusi Eka Afri (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2020)
This study aims to produce valid guided discovery-based math worksheets on rectangular material. This type of research is development research. This research consists of three stages of development, definition, design, and development. This study's subjects were class VII students of SMP Negeri 3 Rambah Hilir in the second semester of the 2019/ 2020 school year. The instrument used in this study was a validation questionnaire sheet. Discovery-based worksheets guide the results of this study. Based on the validity test of the guided discovery-based student worksheet carried out on three validators with several revisions and improvements, the average score of the guided discovery-based student worksheet validation was 3.73 with a very valid category. So it can be concluded that guided discovery-based worksheets are very valid.